The reaction of Portuguese Municipalities to the reestablishment of land customs with Castille in 1591-92. Histories of resistance, neutrality and adaptation - Ribeiro, Ana Sofia (Cuadernos de Historia Moderna, 2022)
One of the conditions agreed between the Portuguese People to acclaim Philip II as king of Portugal at Tomar in 1581 was the suppression of the export/import tax in the land border between Portugal and Castile. Nevertheless, in 1591 the monarch has decided to charge the tax again and restrict the land trade between the two kingdoms, due to the scarcity of fiscal resources in the Treasure of the Monarchy to support the Hispanic expansionist policy. This article unveils the reactions to this measure in four Portuguese municipalities, as well as their motivations. Departing from the point of view granted by the local archives and documents produced by the central institutions in Portugal and in the center of the Monarchy, this article underlines strategies of resistance, adaptation and neutrality chosen by the Portuguese cities regarding this issue and how these strategies conditioned the policy of the Habsburg Monarchy.
Keywords: Land customs; resistance; trade; Porto; negotiation